Characterization of metamorphic basement in the eastern part of Brazo Huemul, province of Neuquén - Gargiulo, M.F. (2006)
This paper describes for the first time in the study area the lithology, structure and different metamorphic events that have affected the basement in the eastern margin of Brazo Huemul of Nahuel Huapi Lake. These rocks have been classified as protomilonitic paragneisses and they were correlated to the Colohuincul Complex. A brittle - ductile shear zone with an orientation of N14°W (similar to the regional trend) has been interpreted as a deep angle reverse fault (74°SW), that put metamorphic basement rocks in tectonic contact with volcanic/ volcaniclastic rocks from Ventana Formation. In agreement with the mineral assemblages observed (quartz - chlorite - biotite - garnet (almandine) - albite) it was possible to determine a sedimentary pelitic protolith that was affected by regional metamorphism under high temperature green schist facies (biotite - garnet zone) conditions. © 2006 Asociación Geológica Argentina.